Main socio-economic and environmental trends in the Carpathian region - Pomázi, István; Szabó, Elemér (Hungarian Geographical Bulletin, 2010)
The authors aim at analysing major socio-economic and environmental processes in the Carpathian region which represents a unique macro-region in Central Europe. The Carpathian countries have experienced major political, economic, social and environmental changes during the past 20 years. Their economy, industry, agriculture and transport sectors were originally developed at accelerated rates, increasing pressures on the environment. Since early 1990s, the GDP, industrial production and agricultural output fell significantly; shrinking economic output contributed to significant reduction of air and water pollution and sudden fall of agricultural chemicals. The most spectacular signs of decoupling can be seen in the case of traditional air pollutants like sulphur dioxide and nitrogen oxides clearly showing effects of fuel mix change. High unemployment, increasing poverty, depopulation of the rural mountain areas are common features in the Carpathians.